PERBANDINGAN METODE PIRAMID NORMAL DAN PIRAMID TERBALIK TERHADAP PENINGKATAN DAYA TAHAN OTOT - Dinda Aliyah Rindahalim, - (2023)
Muscular endurance is a muscle ability that aims to carry out continuous contractions with appropriate training intensity, to support the performance of athletes and non-athletes. This study aims to examine the effect of the normal and inverted pyramid training methods on increasing upperbody and lowerbody muscle endurance after using the normal and inverted pyramid training methods. The research method uses the experimental method The Two- Group Pretest-Posttest Design. The sample used was 20 students of Sports Science FPOK UPI. The instruments used to measure increased muscle endurance are wall squats (lower body) and push up (upper body). The results of this study indicate that the normal pyramid training method and the inverted pyramid training method provide a significant increase in muscle endurance strength, with a significant level of 0.001, which means that the increase in upperbody and lowerbody muscle endurance strength increases significantly.